Muslim marriage and divorce: recounting married women’s quest for individual sovereignty in literary and legal arenas of Bangladesh - Nazmul, Nafisa (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2018.